Sistem Pendukung Pengambilan Keputusan Kesesuaian Beasiswa Menggunakan Naive Bayes - Tan, Yohanes Christianto Aryo Wicaksono; YB Dwi Setianto (Praxis : Jurnal Sains, Teknologi, Masyarakat dan Jejaring, 2020)
Until now there are no system that helps determine candidates who are eligible to receive the Sandjojo Foundation scholarship at Soegijapranata Catholic University. Therefore, scholarship recipients are sometimes not on target. This research can help solve problems by using the Naive Bayes algorithm as a medium for decision makers with criteria such as based on the student's GPA, the total income of parents, and must be an active student in the organization. Using previous registrant data, the Naive Bayes algorithm can study the data for each of the criteria entered to determine whether applicants qualify or not to receive scholarships from the Sandjojo Foundation. This research was made using a web-based application and has been tested four (4) times with a variety of test and training data, with an accuracy of around 50% to 65% and a time of less than three (3) seconds..